Problematika Manajemen Kelas Pendidikan Agama Kristen dan Pengembangan Kerangka Konseptual Berbasis Panggilan Pelayanan Guru - Dominggus Alli Manu; Anka Surya (STT Internasional Harvest Tangerang, 2025)
Classroom management in Christian Religious Education faces complex challenges, particularly due to the lack of integration between pedagogical, relational, and spiritual dimensions in learning practices in the digital era. This condition indicates a gap between the transformative goals of learning and classroom management practices that remain largely technical and administrative. This study aims to analyze the problems of classroom management in Christian Religious Education and to formulate a conceptual framework that is relevant to contemporary learning contexts. This study employs a descriptive qualitative approach through a literature study to examine relevant and recent scholarly sources. The thesis of this study is that classroom management in Christian Religious Education needs to be reconstructed through the integration of pedagogical approaches and the teacher’s calling to serve. The findings indicate that effective classroom management requires the integration of relational, pedagogical, spiritual, and contextual dimensions in learning practices. The conclusion of this study affirms that a conceptual framework based on the calling to serve can serve as a foundation for developing a more holistic and transformative classroom management approach. This study recommends further empirical research to test and develop the proposed conceptual framework in diverse contexts.